Caveolin-1 and Caveolin-2 Can Be Antagonistic Partners in Inflammation and Beyond - de Almeida, Cecília Jacques Gonçalves (Frontiers in Immunology, 2017)
Caveolins, encoded by the CAV gene family, are the main protein components of caveolae. In most tissues, Cav-1 and Cav-2 are co-expressed, and Cav-2 targeting to caveolae depends on the formation of hetero-oligomers with Cav-1. Notwithstanding, Cav-2 has unpredictable activities, opposing Cav-1 in the regulation of some cellular processes. While the major roles of Cav-1 as a modulator of cell signaling in inflammatory processes and in immune responses have been extensively discussed elsewhere, the aim of this review is to focus on data revealing the distinct activity of Cav-1 and Cav-2, which suggest that these proteins act antagonistically to fine-tune a variety of cellular processes relevant to inflammation.